Patient-reported outcomes in advanced NSCLC before and during the COVID-19 pandemic: real-world data from the German prospective CRISP Registry (AIO-TRK-0315) - Sebastian, Martin; Eberhardt, Wilfried E. E.; Heyde, Eyck von der; Dörfel, Steffen; Wiegand, Jörg; Schiefer, Clemens; Losem, Christoph; Jänicke, Martina; Fleitz, Annette; Zacharias, Stefan; Kaiser-Osterhues, Anja; Hipper, Annette; et al. (International journal of cancer, 2024)
Patients with lung cancer under treatment have been associated with a high risk of COVID-19 infection and potentially worse outcome, but real-world data on patient-reported outcomes (PROs) are rare. We assess patients' characteristics and PROs before and during the COVID-19 pandemic in an advanced non-small cell lung cancer (NSCLC) cohort in Germany. Patients with locally advanced or metastatic NSCLC from the prospective, multicentre, observational CRISP Registry (NCT02622581) were categorised as pre-pandemic (March 2019 to Feb 2020, n = 1621) and pandemic (March 2020 to Feb 2021, n = 1317). From baseline to month 15, patients' health-related quality of life (HRQoL) was assessed by FACT-L, anxiety and depression by PHQ-4. Association of pandemic status with time to deterioration (TTD) in QoL scales adjusted for potential covariates was estimated using Cox modelling. PROs were documented for 1166 patients (72%) in the pre-pandemic, 979 (74%) in the pandemic group. Almost 60% of patients were male, median age was 66 years, comorbidities occurred in 85%. Regarding HRQoL, mean-change-from-baseline plots hardly differed between both samples. Approximately 15%-21% of patients reported anxiety, about 19%-27% signs of depression. For the pandemic group, TTD was slightly, but statistically significantly, worse for the physical well-being-FACT-G subscale (HR 1.15 [95%CI 1.02-1.30]) and the anxiety-GAD-2 subscale (HR 1.14 [95%CI 1.01-1.29]). These prospectively collected real-world data provide valuable insights into PROs before and during the COVID-19 pandemic in advanced NSCLC. For the patients, the pandemic seemed to be less of a burden than the disease itself, as there was a considerable proportion of patients with anxiety and depression in both groups.
Zuerst veröffentlicht: 08. Februar 2024
Gesehen am 26.06.2024